Aleksaa60
Rozwiązane

Opuść nawiasy, a następnie wykonaj redukcję wyrazów podobnych:
a) 7k-(m-2n+k) - (5k-3)
b) 5a + (5-8b+2a) - ( - b+1)
c) 0,75-(0,25x+0,5)
d) 3ab - (a+2ab-7a) +ab-a
e) (7xy +8y) - (-10xy+5x) - ( 4xy+3x+5y)
f) 4a+(3a-4b) - (4a+3b)- (-3b-4a)



Odpowiedź :

Odpowiedź:

a) 7k-m+2n-k-5k+3=k-m+2n+3

b) 5a+5-8b+2a+b-1=7a+4-7b

c) 0,75-0,25x-0,5=0,25-0,25x

d) 3ab-a-2ab+7a+ab-a=2ab+5a

e) 7xy+8y+10xy-5x-4xy-3x-5y=13xy+3y-8x

f) 4a+3a-4b-4a-3b+3b+4a=7a-4b

Odpowiedź:

a) 7k - (m - 2n + k) - (5k - 3) = 7k - m + 2n - k - 5k + 3 = k - m + 2n + 3

b) 5a + (5 - 8b + 2a) - (-b + 1) = 5a + 5 - 8b + 2a + b - 1 = 7a - 7b + 4

c) 0,75 - (0,25x + 0,5) = 0,75 - 0,25x - 0,5 = - 0,25x + 0,25

d) 3ab - (a + 2ab - 7a) + ab - a = 3ab - a - 2ab + 7a + ab - a = 2ab + 5a

e) (7xy + 8y) - (- 10xy + 5x) - (4xy + 3x + 5y) =

    = 7xy + 8y + 10xy - 5x - 4xy - 3x - 5y = 13xy - 8x + 3y

f) 4a + (3a - 4b) - (4a + 3b) - (- 3b - 4a) =

   = 4a + 3a - 4b - 4a - 3b + 3b + 4a = 7a - 4b

Szczegółowe wyjaśnienie:

Inne Pytanie